O impacto da ocorrência de palavras ambíguas em português no processo tradutório para Libras via glosas: em debate a palavra estado - Rosa, Keli Adriana Vidarenko da (2014)
The research presented here was focused on reflections and analyses involving the translation of lexical ambiguity between two languages of different modality: we refer to the Portuguese Language and Brazilian Sign Language Libras; more specifically our focus is on the word "state." In such a context, as well as in translations of which take part two oral auditory languages, the translation involving Portuguese and Libras requires the translator a judicious and careful analysis of their lexical choices at the moment often he is translating the source text message to the target text. In this task the t ambiguous lexical items that need to be properly understood in the source language for the translation to happen no meaning problems in the target language. Hence the interest in analyzing the strategies used for the translation of "state" can happen without causing any problems of meaning in the target language. For our analysis, we rely on a corpus consisting of 774 sentences, which were subjected to linguistic analysis and translation into Libras glosses by a professional listener in accordance with Decree 5.626/05. The basis for our discussion is in the main concepts underlying the translation process under the assumptions of authors such as Campos(1986), Quadros (2001, 2004), Oustinoff (2011), Rónai (1976) and Jakobson (1975), and authors who studied lexical ambiguity, as Ullmann (1964), Azeredo (2011) and Silva (2006)